In vitro sustained release of novel natriuretic peptide from solvent evaporation delivery system - Ong, Crystal Li En (2016)
Solvent evaporation technique has been widely studied and is an established method for producing biodegradable Nano or micro particles for pharmaceutical applications. Biodegradable polymers such as poly (lactic-co-glycolic acid) (PLGA) is commonly used as drug carriers due to its biodegradability without any toxic by products, which can be tailored for use as sustained drug delivery systems.